The Effect of Project Based Learning on Creative Writing Skills in Elementary School Students: Multivariate Analysis of Variance on Themes, Diction, Imagination - Retno Winarni (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Problems of creative writing are found in the mastery of themes, diction, and imagination. The Project-based Learning model is proposed as an effective model to improve mastery of themes, diction, and imagination. This study aims to determine the effect of the PjBL model on the mastery of themes, diction, and imagination in fourth grade elementary school students. The research sample consisted of 150 randomly selected. The research location is in Surakarta City. This type of research is quasi-experimental with Posttest Only Control Group Design. Data was collected using a creative writing skills test including indicators of theme, diction, and imagination. Analysis of research data using the multivariate Analysis of Variance (MANOVA) test. Prerequisite tests are carried out by normality and homogeneity tests using the variant matrix test (Box's M). The hypothesis test applies the MANOVA test and is continued with the Post Hoc test. The results of the study concluded that: the PjBL model has a significant effect on creative writing skills in mastering aspects of themes, diction, and imagination both simultaneously and partially. This research recommends teachers apply the PjBL model in increasing student creativity, especially in producing products in the form of creative writing. Keywords: Project-Based Learning, Creative Writing Skills, Multivariate Analysis